Geothermal flow in the western part of the Black Sea. - Kondyurin, A V; Sochel'nikov, V V (PANGAEA, 1983)
Results of heat flow measurements are presented. On the basis of new data on structure of the sedimentary sequence, corrections are introduced that take account of effect of sedimentation. Diagrammatic maps of distribution of observed and deep-seated heat flow have been constructed. A hypothesis is offered that the regional zone of anomalously high heat-flow values on the northern continental slope has been controlled by processes of subsidence of an oceanic plate beneath its continental counterpart.
(Table 1) Heat flow data in the western Black Sea
Keywords: Akademik Kurchatov; AKU26A; Archive of Ocean Data; ARCOD; Black Sea; Conductivity, thermal; Heat flow; Liman-7904; Liman-7905; Liman-7906; Liman-7907; Liman-7908; Liman-7909; Liman-7910; Liman-7911; Liman-7912; Liman-7914; Liman-7915; Liman-7916; Liman-7928; Liman-7929; Liman-7930; Liman-7933; Liman-7934; Liman-7936; Liman-7938; Liman-7940; Liman-7945; Liman-7946; Liman-7948; Liman-7949; Liman-7950; Liman-7951; MULT; Temperature (thermal) gradient